Epidemiological profile of congenital and gestational syphilis cases in the State of Piauí, Brazil - Coeli Vitorino Sales, Magda; Vasconcelos Gomes, Adriana; Miranda Amorim, Fernanda Cláudia; Macêdo Magalhães, Juliana; Ribeiro Gonçalves, Maria Elizabeth; Cavalcante Muniz Lira, Roberta (O Mundo da Saúde, 2022)
This study aimed to identify the epidemiological profile of congenital syphilis in pregnant women residing in the State of Piauí from 2007 to 2017. An ecological epidemiological study was carried out between January and February 2019 in the Notifiable Diseases Information System and the Live Births Information System. The incidence of congenital syphilis increased during the period studied (2007 to 2017), with an emphasis in the “Entre Rios” Health Region. Regarding neonates, they were predominantly diagnosed with up to 6 days of life (94.5%), males (49.9%), mixed race/color (66.4%), recent syphilis (82.8%), and evolved to live (91.9%). Pregnant women are aged between 20 and 39 years (69.9%), brown color (70.5%), low schooling (28.9%), underwent prenatal care (85.4%), received diagnosis during prenatal care (46.6%), did not undergo a treponemal test (46.2%), the non-treponemal test was reactive (86.8%), had a primary form of the disease (30.5%), and partners without treatment (60.8%). It is necessary to improve surveillance and prenatal care actions that result in the planning and adoption of interventions in order to change this epidemiological picture.